An intermolecular hydrogen bond plays a determining role in product selection of a surface confined Schiff-base reaction. Issue 53 (8th June 2021) - Chen, Huamei; Feng, Guangyuan; Liang, Qiu; Zhang, Enbing; Shen, Yongtao; Lei, Shengbin; Hu, Wenping
Abstract : Herein, we illustrate how the cooperation of intermolecular hydrogen bonds and conformation flexibility leads to the formation of diverse complex covalent nanostructures on the surface, while the relative abundance of the final products can be further tuned by adjusting the molar ratio and concentration of monomers. Abstract : Herein, we illustrate how the cooperation of intermolecular hydrogen bonds and conformation flexibility leads to the formation of diverse complex covalent nanostructures on the surface, while the relative abundance of the final products can be further tuned by adjusting the molar ratio and concentration of monomers.